Assessment of academics' use and degree of knowledge regarding the use of Over-The-Counter (OTC) medicines (Research, Society and Development, 2025)
This study seeks to understand how university students use and perceive Over-the-Counter (OTC) medications across different academic programs. The study sample consisted of 51 undergraduate students, and data were collected using a questionnaire containing eight objective questions. Data analysis was performed using descriptive statistics. A higher participation of female students was identified, with ages ranging from 18 to 25 years. Although 74.5% reported having knowledge about OTC medications, 52.9% demonstrated difficulties in their proper use. The most frequently mentioned medications were Dipyrone, Paracetamol, and Dorflex, mainly used to treat pain, fever, and cramps. Regarding guidance, 56.9% stated that they did not receive any type of instruction when purchasing the medication, while 27.3% reported receiving guidance only from pharmacy attendants. The findings reveal the frequent and often inappropriate use of these medications, highlighting the need for educational actions to promote the rational use of OTC drugs among students.